ENHANCING THE PROFITABILITY OF A VERTICALLY INTEGRATED WOOD PRODUCTS PRODUCTION SYSTEM. PART 1. A MULTISTAGE MODELLING APPROACH. - CARINO, HONORIO F. ; WILLIS III, DONALD B.
A MULTISTAGE MODELLING APPROACHA TO PRODUCTION AND INVENTORY PROBLEMS INHERENT IN VERTICALLY INTEGRATED WOOD PRODUCTS MANUFACTURING OPERATIONS IS DISCUSSED IN THIS FIRST INSTALLMENT OF A TWO-PART ARTICLE...